Implementation of External Quality Assessment Scheme in Clinical Chemistry for District Laboratories in Bhutan - Jamtsho, Rixin (Indian J Clin Biochem, 2012)
External Quality Assessment Scheme (EQAS) involves evaluation of a number of laboratories by an outside agency on the performance of a number of laboratories based on their analytical performance of tests on samples supplied by the external agency. In developing countries, establishment of national EQAS by preparing homemade quality control material is a useful scheme in terms of resources and time to monitor the laboratory performance. The objective of this study is to implement an EQAS to monitor the analytical performance of the district laboratories in Bhutan. Baseline information was collected through questionnaires. Lyophilized human serum including normal and abnormal levels were prepared and distributed to 19 participating laboratories. Nine routine analytes were included for the study. Their results were evaluated using Variance index scores (VIS) and Coefficient of variations (CV) was compared with Clinical Laboratory Improvement Act (CLIA) Proficiency Testing Criteria (PT) for each analyte. There was significant decrease in CV at the end of the study. The percentages of results in acceptable VIS as ‘A’ were 63, 60, 66, 69, 73 and 74, 75, 76 and 79 % in November 2009–July 2010 respectively. From our results, we concluded that, establishment of EQAS through distribution of home-made quality control material could be the useful scheme to monitor the laboratory performance in clinical chemistry in Bhutan.